2019
DOI: 10.3390/antiox8090358
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Induction in Postharvest Banana Fruits in Response to NO Donor SNP Occurs via l-Arginine Mediated Pathway and Not via Competitive Diversion of S-Adenosyl-l-Methionine

Abstract: Nitric oxide (NO) is known to antagonize ethylene by various mechanisms; one of such mechanisms is reducing ethylene levels by competitive action on S-adenosyl-L-methionine (SAM)—a common precursor for both ethylene and polyamines (PAs) biosynthesis. In order to investigate whether this mechanism of SAM pool diversion by NO occur towards PAs biosynthesis in banana, we studied the effect of NO on alterations in the levels of PAs, which in turn modulate ethylene levels during ripening. In response to NO donor so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Increased polyamine levels were observed under nitrate nutrition, which resulted in enhanced NO production and associated increased plant disease resistance (Mur et al, 2019). NO-induced polyamine accumulation also plays a role in the delay of fruit ripening (Lokesh et al, 2019). Collectively, these findings suggest that NO is emerging as a key regulator for amino acid metabolism and associated polyamine biosynthesis.…”
Section: No Regulates Amino Acid Metabolism and Polyamine Productionmentioning
confidence: 89%
See 1 more Smart Citation
“…Increased polyamine levels were observed under nitrate nutrition, which resulted in enhanced NO production and associated increased plant disease resistance (Mur et al, 2019). NO-induced polyamine accumulation also plays a role in the delay of fruit ripening (Lokesh et al, 2019). Collectively, these findings suggest that NO is emerging as a key regulator for amino acid metabolism and associated polyamine biosynthesis.…”
Section: No Regulates Amino Acid Metabolism and Polyamine Productionmentioning
confidence: 89%
“…SAM is a common precursor for both ethylene and PA biosynthesis. Recently, it has been shown that, in banana fruit, the biosynthesis of PAs occurs via L-arginine-dependent pathways, but not via competitive diversion of SAM (Lokesh et al, 2019). Interestingly, NO fumigation of tomato fruits with NO gas reduced hydrogen peroxide-scavenging capacity, elevated the levels of antioxidants, such as ascorbate, and enhanced NOmediated PTMs, such as protein S-nitrosylation (Zuccarelli et al, 2021).…”
Section: No Regulates Ethylene Biosynthesis and Polyamine Function In...mentioning
confidence: 99%
“…In banana, PA biosynthesis via an ADC-catalyzed branch is up-regulated several-fold in response to treatment with the NO donor sodium nitroprusside (SNP). NO induces PA biosynthesis via the l-arginine-mediated route rather than via diversion of the SAM pool, indicating that NO may enhance PA levels via ADC during ripening ( Lokesh et al, 2019 ). Taken together, PA catabolism produces H 2 O 2 , which is closely linked to ABA, NO, and Ca 2+ , thereby opening new signaling pathways for exploration into their roles during fruit ripening and senescence.…”
Section: Mechanisms Of Pa Action In Ripening Senescence and Qualitymentioning
confidence: 99%
“…By analyzing in vitro pepper catalase, the authors found that the activity of this antioxidant enzyme is negatively modulated by S -nitrosation and nitration. Lokesh et al [13] study how the exogenous application of NO triggers polyamine accumulation in postharvest banana ( Musa acuminate ) fruit, apparently via the arginine-mediated route. Meanwhile, the study by Geng et al [14] shows that H 2 S content is modulated by NO in peach ( Prunus persica ) fruit during cold storage, whose quality is adversely affected by the chilling injury phenomenon.…”
mentioning
confidence: 99%